Sampling chronology of hydroponics lettuce plants for adjusting vegetative growth curves - Lopes, Sidinei José; Santos, Paula Machado dos; Storck, Lindolfo; Cocco, Carine; Damo, Henrique Perin; Martini, Luís Fernando Dias (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to determinate a sampling chronology to adjust lettuce hidroponic growth curves during its vegetative development. The variety Regina was grown from September 8, 2004 until November 19, 2004 (spring/summer) and February 22, 2005 until May 24, 2005 (summer/fall). Plants were placed inside a plastic covered greenhouse in Santa Maria, RS, Brazil. Based on the adjusted cosine model, daily samples were taken as standard and different sampling intervals were simulated in order to better adjust the same model. To estimate de adequate sampling interval a comparison was conducted between the variance of lack of adjustment of the daily sampling with the variance of lack of adjustment of different samplings intervals using an F test. Sampling chronograms for adjusting crop growth curves of hydroponics lettuce plants for both spring/summer and summer/fall seasons present a time interval of two days for total plant or leaf dry weight and four days intervals for root dry weight or leaf area.